2016
DOI: 10.1136/archdischild-2016-311535.1
|View full text |Cite
|
Sign up to set email alerts
|

The Potential for Pharmacists to Manage Children Attending Emergency Departments

Abstract: Paediatric patients attending Emergency Departments were judged by pharmacists to be suitable for management outside a hospital setting in approximately 1 in 11 cases, and by hospital independent prescriber pharmacists in 4 in 10 cases. With further training, it was found that the total proportion of cases that could be managed by a pharmacist was 45%. The greatest impact for pharmacist management occurs in general medicine and orthopaedics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The literature identifies the possibility of an increased role for pharmacists in dealing with acutely unwell children. One UK study showed that 9% of ED attendees were appropriate for treatment by community pharmacists instead [ 24 ]. Similarly, 15% of consultations with children attending general practices in the UK were deemed unnecessary as opposed to just 6% in adults [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…The literature identifies the possibility of an increased role for pharmacists in dealing with acutely unwell children. One UK study showed that 9% of ED attendees were appropriate for treatment by community pharmacists instead [ 24 ]. Similarly, 15% of consultations with children attending general practices in the UK were deemed unnecessary as opposed to just 6% in adults [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…A previous UK study found that 9% of paediatric cases attending Emergency Departments (ED) could have been clinically managed by community pharmacists (Terry et al., 2016). There remains a lack of awareness of CP services by parents and young people (YP).…”
Section: Introductionmentioning
confidence: 99%